2000
DOI: 10.1067/mva.2000.107310
|View full text |Cite
|
Sign up to set email alerts
|

Skin perfusion pressure of the foot is a good substitute for toe pressure in the assessment of limb ischemia

Abstract: We concluded that SPP measured in the foot correlates well with toe pressure and can be substituted for toe pressure measurement in patients in whom toe pressures cannot be measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 16 publications
0
67
0
Order By: Relevance
“…This arm of the immune system is responsible for the rapid initiation and fast progression of acute diseases like ARDS. Specific factors that must be addressed when translating animal data to estimate human innate immune responses include differences in production of nitric oxide (Schneemann et al 1993;Schromm et al 2000;Thoma-Uszynski et al 2001) and chemokines (Zlotnik and Yoshie 2000;Tsai et al 2000) as well as expression of chemokine receptors (Fan et al 2007) and Toll-like receptors (Rehli 2002). Large differences exist among different mouse strains and genetically engineered mice with regard to the immune system (reviewed in Sellers et al 2012;Seymour, Sundberg, and Hogenesch 2006), and these differences can impact the pattern of lesions when modeling ARDS (Matute-Bello, Frevert, and Martin 2008;Goldman et al 2014).…”
Section: Principal Features Used To Define Ards In Animal Modelsmentioning
confidence: 99%
“…This arm of the immune system is responsible for the rapid initiation and fast progression of acute diseases like ARDS. Specific factors that must be addressed when translating animal data to estimate human innate immune responses include differences in production of nitric oxide (Schneemann et al 1993;Schromm et al 2000;Thoma-Uszynski et al 2001) and chemokines (Zlotnik and Yoshie 2000;Tsai et al 2000) as well as expression of chemokine receptors (Fan et al 2007) and Toll-like receptors (Rehli 2002). Large differences exist among different mouse strains and genetically engineered mice with regard to the immune system (reviewed in Sellers et al 2012;Seymour, Sundberg, and Hogenesch 2006), and these differences can impact the pattern of lesions when modeling ARDS (Matute-Bello, Frevert, and Martin 2008;Goldman et al 2014).…”
Section: Principal Features Used To Define Ards In Animal Modelsmentioning
confidence: 99%
“…Castronuovo, et al defined an SPP of 30 mmHg as a borderline for the diagnosis of ischemic ulcer, and reported that wound healing can be expected in about 80% of patients with an SPP of 30 mmHg and 95% or more of patients with an SPP of 40 mmHg. [2][3][4] In our patients, also, the SPP improved to 30 mmHg or higher in 23 limbs with the exception of 1 limb after paramalleolar bypass, and ulcers and wounds healed in all patients, with no major amputation.…”
Section: Discussionmentioning
confidence: 81%
“…[2][3][4] In this study, we evaluated the effects of DM and HD on the improvement in the foot blood flow in CLI patients with tissue loss after bypass surgery by comparing changes in the SPP between before and after surgery among those with DM, HD, and no DM or HD. Regarding endovascular treatment, which has recently begun to be performed frequently for CLI, Iida, et al compared direct (revascularization of the ulcerated area) and indirect (revascularization out of the ulcerated area) groups, and reported that the SPP increased significantly with a higher limb salvage rate in the direct than in the indirect group (82% vs. 64%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…As with the above mentioned studies, this group also found a threshold of 40mmHg as predictive of healing ulceration or gangrene but with a slightly lower sensitivity and specificity (72% and 88%, respectively) (Yamada, et al 2008). In 85 limbs of 71 patients referred to a vascular laboratory, skin perfusion pressure measurement was found to correlate closely with toe pressure measurements (Tsai, et al 2000), allowing substitution of SPP for toe pressures. This is a significant benefit in certain circumstances since it may be impractical to determine toe pressures due to the commonality of wounds on the toes.…”
Section: Skin Perfusion Pressurementioning
confidence: 78%